New information about the toxicological profile of Prorocentrum panamense (Prorocentrales, Dinophyceae) and its global distribution. Issue 2 (7th February 2022) - Gaiani, Greta; Rey, María; Tudó, Àngels; Rambla, Maria; Diogène, Jorge; Campàs, Mònica; Alcaraz, Carles
SUMMARY: Dinoflagellates of the genera Prorocentrum and Dinophysis are known producers of toxic compounds belonging to the okadaic acid (OA) group. The ingestion of shellfish contaminated with these toxins causes a human disease named diarrheic shellfish poisoning (DSP). In this study, the first record of Prorocentrum panamense, a potential toxin‐producer species, was reported in the Canary Islands together with its toxicological characterization. Prorocentrum panamense cells were collected during April 2017 from natural pools located in the Northeastern part of Gran Canaria. This new record represents an expansion of P. panamense distribution area, previously restricted to the Pacific Ocean, Indian Ocean, Arabian Gulf and the Caribbean, and its introduction mechanisms are discussed. Laboratory cultures of P. panamense were settled and toxin production was assessed in both cell pellets and culture media at four different growth phases (latency, exponential, early stationary and late stationary) implementing LC‐MS/MS and neuro‐2a cell‐based assay (CBA). LC‐MS/MS allowed the identification of OA in the fraction corresponding to the late stationary phase, and tests performed on neuro‐2a cells showed, for most of the fractions, OA‐like activity observable by both cell morphology changes and cell mortality. This information is fundamental for a better understanding of the genus Prorocentrum global distribution, its ecology, and risks associated to toxic producing species.